Pengaruh Gaya Kepemimpinan Dan Motivasi Kerja Terhadap Kinerja Guru Smkn Bantarkalong Kabupaten Tasikmalaya - Ratih Lulu Lestari; Kusuma Agdhi Rahwana; Dudu Risana (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2023)
Performance is the output or final result of work done by employees in a certain period, the work done by employees must be in accordance with the provisions set by the organization for their employees. This study aims to determine the effect simultaneously or partially of the Leadership Style variable and the Work Motivation variable on the measured performance. The population used in this study was 45 Bantarkalong Vocational High School teachers. The method used in this research is descriptive research with a quantitative approach. Sample selection using saturated samples. The sample used is the entire population, namely 45 Bantarkalong Vocational High School teachers. Sources of data in this study are secondary data and primary data. The data analysis technique used is multiple linear regression with the help of SPSS 26. Based on the results of the study it was concluded that Leadership Style and Work Motivation simultaneously have a significant effect on performance. Leadership style partially has a significant effect on performance. Work motivation partially has a significant effect on performance.